استكشاف تصورات طلبة كلية التربية عن التدريس الاضطراري في أثناء وباء كوفيد ١٩: دراسة القدرة على التعلم الذاتي في ضوء النوع والتخصص = Exploring KOED students’ perceptions regarding emergency education during the COVID-19 pandemic: a study of self-directed learning ability according to gender and academic specialization - Karawani, Muslima Saleh; Preece, Abdul Shakour Duncan (IIUM Press, 2023)
This study examines the perceptions of students regarding remote teaching and learning (RTL) during the COVID-19 pandemic, specifically synchronous and asynchronous teaching, and their relationship to students' self-directed learning abilities. The study sample consisted of 318 undergraduate students from four disciplines: curriculum and instruction, guidance and counseling, teaching English as a second language, and teaching Arabic as a second language. Data were collected through an online survey and advanced statistical analysis techniques including descriptive statistics and parametric analysis were used for data analysis. The research findings indicate that students had a positive outlook on their experiences, but synchronous RTL sessions were rated higher than asynchronous RTL sessions. Despite differences in gender and specialization, students provided high ratings for self-directed learning, suggesting that instructors need to enhance asynchronous RTL to improve students' self-directed learning abilities.